Resposta do feijoeiro (Phaseolus vulgaris L.) ao molibdênio e ao cobalto em solos de Viçosa e Paula Cândido, Minas Gerais - Baêta dos Santos, Alberto; Vieira, Clibas; Gomide Loures, Emílio; Braga, José Mário; T L Thièbaut, José (Revista Ceres, 2025)
The effect of molybdenum and cobalt on beans (Phaseolus vulgaris L. cv. Ricobaio 1014) was studied under greenhouse conditions. Two soils from Viçosa and one from Paula Candido, Minas Gerais, Brazil, were used.